Measuring the Redshift-space Distortions by Cross-correlating the Density Fields Before and After Reconstruction - Weibing Zhang; Ruiyang Zhao; Xiaoyong Mu; Kazuya Koyama; Ryuichi Takahashi; Yuting Wang; Gong-Bo Zhao (The Astrophysical Journal)
In this work, we develop a theoretical model for the cross-power spectrum of the matter density field before and after standard baryonic acoustic oscillation reconstruction. Using this model, we extract the redshift-space distortion parameter from the cross-power spectrum. The model is validated against a suite of high-resolution N -body simulations, demonstrating its accuracy and robustness for cosmological analyses.